Competing crystallization of α- and β-phase induced by β-nucleating agents in microdroplets of isotactic polypropylene. Issue 10 (24th February 2022) - Carmeli, Enrico; Ottonello, Sara; Wang, Bao; Menyhárd, Alfréd; Müller, Alejandro J.; Cavallo, Dario
Abstract : Crystallization of heterogeneously nucleated isotactic polypropylene microdroplets in an immiscible polystyrene matrix allows the estimation of intrinsic nucleating efficiency of nucleating agents promoting the formation of different polymorphs. Abstract : The nucleation efficiency of substrates towards a specific polymer is usually based on empirical methods, which depend on the employed experimental conditions. A more quantitative method to study the efficiency of nucleating agents promoting polypropylene β-phase is reported here. When a polymer is dispersed into sufficiently small droplets, the overall crystallization kinetics is controlled by nucleation, as growth can be orders of magnitude faster than nucleation. Confinement of polypropylene containing the nucleating agent particles into micro-domains ( i.e., droplets) within a polystyrene matrix allows the isolation of the nucleation process and the determination of the surface free energy difference, Δ σ . This parameter describes the intrinsic nucleation efficiency of a particular nucleating agent. Isothermal crystallization measurements were performed for dispersed polypropylene droplets containing three nucleating agents which catalyze the formation of both α- and β-phase ( N, N ′-dicyclohexylterephthalamide, quinacridone quinone, and tris-2, 3-dimethyl-hexylamide of trimesic acid), and the data were analyzed via a first-order kinetics model. According to the calculated Δ σ values, the nucleating efficiency scale is DCHT > TATA > QQ for α-phase, while DCHT > QQ for β-phase, in spite of the higher total amount of β-crystals generated by QQ particles.